miR-26 inhibits proliferation and promotes apoptosis of multiple myeloma cells by targeting BNIP3: miR-26 suppresses myeloma cell growth via BNIP3 targeting - Zhou, Meiyu; Deng, Tianxia; Tan, Yonghong; Liu, Li; Wang, Mingxia (Cellular and Molecular Biology, 2023)
This study was carried out to investigate the molecular mechanism of microRNA-26 (miR-26) targeting BNIP3 to mediate proliferation and apoptosis of multiple myeloma (MM) cells. The expression of miR-26 and BNIP3 in MM and normal tissues was detected by qRT-PCR and Western blot. According to the average expression of miR-26 and BNIP3, the patients were divided into 12 cases with high miR-26 expression group, 18 cases with low miR-26 expression group, 20 cases with BNIP3 high expression group, and 10 cases with BNIP3 low expression group. The correlation between the expression of miR-26 and BNIP3 and the clinicopathological characteristics of MM patients was compared and analyzed. The effect of up-regulation of miR-26 expression and BNIP3 overexpression on the proliferation of multiple myeloma cells RPMI8226 was examined by MTT assay. Flow cytometry was used to detect the effect of miR-26 expression and BNIP3 overexpression on the apoptosis of RPMI8226 cells. The dual luciferase reporter assay validated the targeted regulation of miR-26 on BNIP3. The expression level of miR-26 in MM tissues was lower than that in normal tissues (P<0.05), and the expression level of BNIP3 in MM tissues was higher than that in normal tissues (P<0.05). miR-26 was closely related to clinical stage, M protein type and light chain type (P<0.05), while BNIP3 was closely related to M protein type and light chain type (P<0.05). After up-regulating miR-26 expression, cell viability was significantly decreased (P<0.05), apoptosis rate was significantly increased (P<0.05) Dual luciferase reporter experiments confirmed that miR-26 could target BNIP3 and negatively regulate the expression of BNIP3 (P<0.05). Overexpression of BNIP3 reversed the effect of up-regulation of miR-26 expression on proliferation and apoptosis of RPMI8226 cells. Up-regulation of miR-26 expression inhibits MM cell proliferation and promotes apoptosis by targeting BNIP3.